Comparative Activities of Selected Beta-Lactam Antibiotics Against Haemophilus influenzae - Jorgensen, James H. (1978)
The comparative activities of ampicillin, cefamandole, cefoxitin, cefaclor, and cefatrizine against both beta-lactamase-producing and non-beta-lactamase-producing isolates of Haemophilus influenzae were determined by using an agar dilution susceptibility test procedure. Ampicillin was the most active drug tested against non-beta-lactamase-producing isolates, whereas cefamandole was most active against beta-lactamase-producing strains.